Review of Financial and Policy Performance Dividend to Company Value - Rante, Yohanes (PT. Riset Press International, 2023)
The consumer goods industry is one of the sectors that can lift the country's economic growth and can survive under any conditions so that it has the best performance opportunities than other sectors. The consumer goods industry has been able to contribute 58% to the country, even though the consumer goods sector index has only decreased by 5.5% in the last 10 years. This research was conducted to determine the effect of financial performance in the form of profitability, leverage, liquidity, and dividend policy on firm value, the theory used is signaling theory. The population uses consumer goods industry sector companies for the 2017-2021 period as many as 76 companies and the sample obtained is 14 companies using a purposive sampling technique. Analysis in this study used SPSS software, data analysis used descriptive statistics, and classic assumption tests included normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. For the hypothesis using, t-test, and the coefficient of determination (R 2 ) using multiple linear regression analysis. The results of this study indicate that profitability and dividend policy have a significant positive effect on firm value, while leverage and liquidity have no significant effect on firm value.